Técnicas de acionamento e controle ótimo aplicados ao motor a relutância chaveado para maximizar o rendimento - Reis, Márcio Rodrigues da Cunha (2020)
This work presents modeling, driving and speed control techniques for the switched reluctance motor. The objective is to improve the computational model, the control response and the machine efficiency. A parametric regression model was used to find the inductance profile of the switched reluctance motor and from the new inductance profile model. The drive and control techniques are shown: i) with classical speed control acting on the excitation voltage and fixed switching angles, ii) with classical speed control acting on the switching angles and fixed excitation voltage and iii) with classical speed control acting on the excitation voltage, in this case, with dynamic switching angles and controller parameters. The inductance profile is represented analytically and inserted into the machine computer model, allowing greater precision and low computational cost. The speed controls acting on the excitation voltage with dynamic controller parameters and dynamic switching angles allowed shorter response time for a wide range of control, higher efficiency, low computational cost and simplified implementation and maintenance. The techniques proposed in this work obtained precision of the computational model with respect to the system (in workbench) and optimized parameters in a wide range of the speed control, allowing an improvement of switched reluctance motor efficiency.